Reasons for Visitor dissatisfaction in National Parks based Tourism in Sri Lanka - Prakash, T.G.S.L.; Perera, P.K.P.; Newsome, D.; Kusuminda, T.G.T. (My University, 2017)
Attached

industry with foreign visitations accounting for the larger share of income of NPs. However, current wildlife tourism practices based on NPs seem to be unsustainable, and cause bad tourism experiences, especially in the case of foreign visitors. This study examined the major causes of visitor dissatisfaction during wildlife tourism experiences at five highly visited NPs in Sri Lanka using reviews posted in the travel website Trip Advisor. Analysis found 15 major causes of visitor dissatisfaction with nearly 75% of negative reviews linking to park management related issues, while the rest stressing on tour-operator related issues. Heavy traffic congestion inside NPs, lack of opportunities to observe diverse wildlife, unreasonable entrance fees, poor implementation of environment and wildlife, poor maintenance of nature trails and lack of quality personal interpretation services were the key park management-related issues highlighted in negative reviews. The major tour-operator related issues include reckless/poor driving by safari vehicle drivers, poor condition of safari vehicles, expensive safari vehicle fees, and dishonest practices of tour operators.
Keywords: national parks, overcrowding, satisfaction, trip advisor, wildlife tourism